Can the Tourism Sector in Libya be Considered as a Locomotive for Sustainable Economic growth? - الحویج, حسين (Dirasat in Economics and Business, 2017)
This research aimed to examine the validity of the "Tourist-led Growth Hypotheses" in the Libyan economy. In order to achieve its objective the research has used the ARDL Model According to the results of Bound Test the research variables has a long-run relationship. In addition, the estimated long run model has demonstrated that the tourism receipts has a weak negative long run relationship with the economic growth. In the short run context the research has estimated UECM Model which has illustrated the same result regarding the main variable "tourism receipts". Furthermore, the research found that the error correction term was 79.4%. Moreover, the Granger Causality test has indicated that the tourism receipts does not cause the Economic growth in Libya. Therefor, the TLG hypotheses is not valid in the case of the Libyan economy. However, the hypotheses that economic growth cause tourism receipts has been supported.